Association between moderate-to-vigorous physical activity and chronic disease risk in adults and elderly: insights from the UK Biobank study - Ng, Kei Shing; Lian, Jie; Huang, Fan; Yu, Yan; Vardhanabhuti, Varut (Frontiers in Physiology, 2024)
BackgroundThis study aimed to determine the associations between different intensities of moderate to vigorous physical activity (MVPA) and the incidence of chronic diseases, and to assess the risk levels associated with these activities over time.MethodsA prospective cohort study (UK Biobank Activity Project) with data collected between June 2013 and December 2015 included 59,896 adults (mean age = 59.68; male = 38.03%) free from chronic diseases. Participants were categorized into tertiles based on their weekly MVPA: lowest (<224 min for males, <143 min for females), medium (224–444 min for males, 143–308 min for females), and highest (≥444 min for males, ≥308 min for females), stratified by gender. The mean onset of chronic disease symptoms occurred at 3.57 years, with participants followed up during this period. Wearable accelerometry data were used to quantify MVPA levels.FindingsLowest tertile of MVPA were significantly correlated with increased risks of chronic disease (24%–110% increased risk) based on odds ratios (ORs), with dose-response relationship observed. In males with the lowest tertile of MVPA, significant associations were identified with type 2 diabetes mellitus (T2DM) (OR = 1.90; CI: 1.44–2.51), neurodegenerative disease (OR = 1.80; CI: 1.19–2.71), metabolic syndrome (OR = 1.34; CI: 1.18–1.53), hypertension (OR = 1.27; CI: 1.12–1.44), and atherosclerotic cardiovascular disease (ASCVD) (OR = 1.24; CI: 1.03–1.49). In females, the lowest tertile of MVPA levels were associated with increased risks of neurodegenerative disease (OR = 2.10; CI: 1.36–3.24), T2DM (OR = 1.88; CI: 1.37–2.58), cerebrovascular disease (OR = 1.61; CI: 1.12–2.29), ASCVD (OR = 1.58; CI: 1.23–2.03), metabolic syndrome (OR = 1.49; CI: 1.32–1.69), and hypertension (OR = 1.44; CI: 1.29–1.61). Longitudinally, the lowest tertile of MVPA in males showed elevated risks for neurodegenerative disease (HR = 2.13; CI: 1.24–3.66), T2DM (HR = 1.83; CI: 1.30–2.57), hypertension (HR = 1.33; CI: 1.15–1.53), metabolic syndrome (HR = 1.32; CI: 1.14–1.54), and ASCVD (HR = 1.29; CI: 1.03–1.61). In females, the lowest tertile of MVPA was associated with similar risks for ASCVD (HR = 1.59; CI: 1.16–2.20), T2DM (HR = 1.57; CI: 1.08–2.29), hypertension (HR = 1.53; CI: 1.34–1.74), and metabolic syndrome (HR = 1.50; CI: 1.29–1.73).ConclusionUsing wearable accelerometry data, this study demonstrated the quantifiable risks of chronic diseases and their development, highlighting the importance of MVPA.